Current Status of Immune Checkpoint Inhibitor Immunotherapy for Lung Cancer - Xiong, Wei; Zhao, Yunfeng; Du, He; Guo, Xuejun (Frontiers in Oncology, 2021)
Immunotherapy is a major breakthrough in the treatment of cancer in recent years. Immune checkpoint inhibitors(ICIs) including programmed death–ligand 1(PD-L1)/programmed death-1(PD-1) and cytotoxic T-lymphocyte antigen-4(CTLA-4) have been used for different histologic types of cancer including primary lung cancer which represents the most common and fatal cancer globally. Among ICIs immunotherapy agents, atezolizumab, durvalumab, ipilimumab, nivolumab, and pembrolizumab are currently used as standard-of-care(SOC) treatment for metastatic or earlier stages of lung cancer. Major issues of ICIs immunotherapy in lung cancer comprise the use of immune biomarker prior to ICIs therapy, selection of ICIs agents, combination of ICIs/chemotherapy, combination of ICIs/radiotherapy, sequence of tyrosine kinase inhibitor(TKI) targeted therapy and ICIs immunotherapy, sequence of chemotherapy and ICIs immunotherapy, treatment duration of ICIs regimen and ICIs therapy for different histopathology, stage, PD-L1, as well as performance status. Based on the contemporary major clinical trials and authoritative guidelines, the objective of this review is to present an overview of the current status of ICIs immunotherapy in lung cancer.